164k views
4 votes
Please help thank youuu

Please help thank youuu-example-1

1 Answer

3 votes

Answer:

f(-7) = -15

g(-3) = 27

Explanation:

We see that the functions defined are:

f(x) = 2x - 1

AND

g(x) = 2x^2 - 3x

This problem asks to find f(-7) and g(-3). To find this, we have to plug the respective numbers into the respective functions.

f(-7) = 2 (-7) - 1

f(-7) = - 14 - 1

f(-7) = -15

g(-3) = 2(-3^2) - 3(-3)

g(-3) = 2(9) + 9

g(-3) = 18+9

g(-3) = 27

FINAL ANSWER: f(-7) = -15, g(-3) = 27

User Nikolay Kostov
by
5.2k points